EFFECT OF SUGARCANE BY-PRODUCT BASED COMPLETE RATIONS ON GROWTH AND CARCASS CHARACTERISTICS IN BUFFALO BULL CALVES - RAGHAVA RAO E, PRASANNA KUMAR R SIVAIAH K (Indian Journal of Animal Production and Management, 2017)
Six rations comprising of five complete rations and one conventional ration (containing chopped hybrid Napier and concentrate mixture) were formulated by using sugarcane byproducts and other crop residues and balanced concentrate mixture in the mash form. These rations were compared by feeding to 24 Murrah buffalo bull calves for a period of 167 days using Randomized Block Design to study the effect of processing of complete diet on growth, nutrient utilization and carcass characteristics. Highest ADG (610.0g.) recorded in buffalo bull calves fed on complete ration-II (Sugarcane tops, maize stover and balanced concentrate mixture) when compared among the complete rations and control. The cost of control ration per kg live wt.gain was Rs.41.14.The cost of complete ration per kg live weight gain was higher in control than complete rations though insignificantly different. The cost of complete ration per kg live weight gain was reduced by Rs.3.11, 8.69, 8.60, 10.92 and 8.10 for complete rations-I, II, III, IV and VI, respectively, when compared to control diet. The dressing percentage on live weight was significantly (P<0.05) lower in bull calves fed on complete rations than those fed on control ration. The dressing percentage and proportions of the wholesale cuts were within the normal range. These results indicated that the sugarcane by-products and other crop residues can be incorporated in the complete rations in growing bull calves without any adverse effects. Further, utilization of agro-industrial byproducts for animal production can be utilized effectively to bridge the gap of roughage shortage in this country. Keywords: Sugarcane